Platelet lysate membranes as new autologous templates for tissue engineering applications - Babo, P. M. (2014)
Platelet lysate (PL) has been increasingly explored in tissue engineering and regenerative medicine fields as a natural source of growth factors and/or as a support for cell growth and differentiation. Despite its tremendous potential, when used as tridimensional scaffolding systems, PL presents an inherent fragility and fast dissolution which hinders its application. The main objective of this work was to develop novel and robust PL-based membranes, crosslinked with genipin, for tissue engineering purposes. The membranes prepared present unique physical and mechanical properties, which indicate that these structures might be used in a vast range of applications. These PL-based structures present a high water uptake and stability over time. Overall, the developed membranes demonstrated a positive in vitro biological response as they were able to support and promote the adhesion and proliferation of human adipose derived stem cells. In addition to their role as supportive matrices for cell culture, the proposed membranes may simultaneously act as a growth factor controlled delivery systems, and thus hold great potential in several approaches for the regeneration of tissues.